Formation of ring marks in stocked tilapia juveniles (Oreochromis aureus/O. niloticus) (Perciformes: Cichlidae) - Ana L Ibañez; Marco A Romo-Coronel (Revista de Biología Tropical, 2007)
Lake Metztitlán was dried up completely in the spring of 1998 and refilled in August of that year. In the period September-November, two cohorts of 1.6 million juveniles of a tilapia hybrid were stocked (Oreochromis aureus/O. niloticus), and monitored every month for one year. Since the date of birth of these juveniles was known, the analyses focused on whether the ring marks of the scales, sagittae and opercula or the circuli of the scales could be used to age them. The ring marks of the scales and opercula showed great variability, and the sagittae had a significant relationship with length, but it is unclear if at least the first ring mark could be formed at the hatchery and reflect changes in diet and/or tank movements in the fish farm. The circuli had a continuous regular behavior, with a formation rate of 10.38±0.93 and 11.38±0.95 circuli/month for the first and second cohorts, respectively. This proportion was maintained during the study period, and could be of help to calculate an approximate age of juveniles, especially in stocked fish that show multiple ring marks because of manipulation in fish farms and stocking events. Rev. Biol. Trop. 55 (3-4): 1005-1013. Epub 2007 December, 28. El lago de Metztitlán se secó completamente en la primavera de 1998, inundándose nuevamente en agosto del mismo año para ser repoblado entre septiembre y noviembre con 1.6 millones de jóvenes de un híbrido de tilapia (Oreochromis aureus/O. niloticus) en dos periodos. Ambas cohortes fueron monitoreadas mensualmente durante un año. Debido a que la fecha de nacimiento era conocida, el objetivo del estudio fue evaluar si las marcas anulares de las escamas, las sagittae y los opérculos, o los circuli de las escamas pueden usarse para estimar la edad. Los anillos de las escamas y opérculos mostraron gran variabilidad, mientras que las de las sagittae se relacionaron significativamente con la longitud, sin embargo no quedó claro si al menos el primer anillo podría haber sido formado por cambios en dieta o movimientos en los tanques de la granja de cultivo. Por el contrario los circuli mostraron una formación regular con una tasa de formación de 10.38±0.93 y 11.38±0.95 circuli/mes para la primera y segunda cohortes, respectivamente, proporción que fue mantenida durante el periodo de estudio y que puede ser usada para calcular la edad de los jóvenes, especialmente en organismos que muestran numerosos anillos debido a la manipulación sufrida en las granjas o debido a las "siembras".